An Economic Analysis of Unemployment in Trinidad and Tobago - Andrew S. Downes (Inter-American Development Bank, Office of the Chief Economist, 1998)
Unemployment is regarded as one of the most challenging economic problems facing the governments of the Caribbean. Although there are variations in the measurement of unemployment, official estimates obtained from labor force surveys indicate that in 1995 the unemployment rate ranged from 7. 8 percent in Antigua/Barbuda to 19. 7 percent in Barbados. This paper explores unemployment in Trinidad and Tobago.
Keywords: 330